Performance analysis of Chilean water companies after the privatization of the industry: the influence of ownership. Issue 1 (2nd January 2022) - Molinos-Senante, Maria; Maziotis, Alexandros; Villegas, Andres
ABSTRACT: This study examines the efficiency and productivity of the Chilean water and sewerage industry over the period 2010–2017 using a stochastic cost frontier model. This methodological approach allowed us to evaluate the impact of water companies´ ownership on their productivity. This is very relevant for the Chilean water and sewerage industry which involves a public, full private and concessionary water companies. The results evidenced that the Chilean water and sewerage industry improved its productivity across years. However, the increase in the productivity of full private and concessionary water companies was larger than the one experienced by the public water company.